The relationship between cash dividend and earnings growth of listed companies in Tehran stock exchange - Kheirandish, Massoud (2022)
Dividend policy is one of the most important financial decisions managers encounter. This study contributes to empirical studies examining the relationship between cash dividends and earnings growth of companies listed on the Tehran Stock Exchange during the period 2007-2020. As a result, 131 companies have been examined with the multiple regression estimation model. The findings show a significant relationship between cash dividends per share and future earnings growth. Furthermore, there is a sig nificant relationship interaction term between the dividend payout ratio and the investment growth assumption. This relationship is also observed for return on equity and dividend payout ratio.